Negative cooperativity in binding of muscarinic receptor agonists and GDP as a measure of agonist efficacy - Jakubík, J; Janíčková, H; El-Fakahany, E E; Doležal, V (British journal of pharmacology, 2011)
BACKGROUND AND PURPOSE: Conventional determination of agonist efficacy at G-protein coupled receptors is measured by stimulation of guanosine-5'-γ-thiotriphosphate (GTPγS) binding. We analysed the role of guanosine diphosphate (GDP) in the process of activation of the M₂ muscarinic acetylcholine receptor and provide evidence that negative cooperativity between agonist and GDP binding is an alternative measure of agonist efficacy. EXPERIMENTAL APPROACH: Filtration and scintillation proximity assays measured equilibrium binding as well as binding kinetics of [³⁵S]GTPγS and [³H]GDP to a mixture of G-proteins as well as individual classes of G-proteins upon binding of structurally different agonists to the M₂ muscarinic acetylcholine receptor. KEY RESULTS: Agonists displayed biphasic competition curves with the antagonist [³H]-N-methylscopolamine. GTPγS (1 µM) changed the competition curves to monophasic with low affinity and 50 µM GDP produced a similar effect. Depletion of membrane-bound GDP increased the proportion of agonist high-affinity sites. Carbachol accelerated the dissociation of [³H]GDP from membranes. The inverse agonist N-methylscopolamine slowed GDP dissociation and GTPγS binding without changing affinity for GDP. Carbachol affected both GDP association with and dissociation from G(i/o) G-proteins but only its dissociation from G(s/olf) G-proteins. CONCLUSIONS AND IMPLICATIONS: These findings suggest the existence of a low-affinity agonist-receptor conformation complexed with GDP-liganded G-protein. Also the negative cooperativity between GDP and agonist binding at the receptor/G-protein complex determines agonist efficacy. GDP binding reveals differences in action of agonists versus inverse agonists as well as differences in activation of G(i/o) versus G(s/olf) G-proteins that are not identified by conventional GTPγS binding.
Keywords: Animals; Muscarinic Agonists; N-Methylscopolamine; agonisté muskarinových receptorů; křečci praví; Kinetics; Muscarinic Antagonists; CHO buňky; guanosindifosfát; vazba proteinů; transfekce; Transfection; proteiny vázající GTP; guanosin 5'-O-(3-thiotrifosfát); lidé; rekombinantní proteiny; GTP-Binding Proteins; Recombinant Proteins; antagonisté muskarinových receptorů; Cricetulus; Receptor, Muscarinic M2; alosterická regulace; N-methylskopolamin; Guanosine 5'-O-(3-Thiotriphosphate); receptor muskarinový M2; radioligandová zkouška; Radioligand Assay; Allosteric Regulation; zvířata; Guanosine Diphosphate; Protein Binding; kinetika; Cricetinae; CHO Cells; Humans